2011
DOI: 10.1016/j.buildenv.2010.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark experiments for moisture transfer modelling in air and porous materials

Abstract: Abstract.The presence of hygroscopic materials has a large impact on the moisture balance of buildings. Nowadays, HAM (Heat, Air and Moisture) models are widely used to investigate the role of hygroscopic materials on the performance of buildings, i.e. on the building envelope, the indoor climate and valuable objects stored within the building. Recently, these HAM models are being coupled to CFD models to study the moisture exchange between air and porous materials on a local scale (microclimates), or to BES (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 36 publications
0
19
0
2
Order By: Relevance
“…By implementing a detailed HAM model into an existing CFD solver (Fluent®) he was able to model the heat and moisture transport in the air and porous material simultaneously. The coupled model was validated using climate chamber experiments [12]. However, Steeman only modelled vapour diffusion as a transport mechanism in the porous material.…”
Section: Introductionmentioning
confidence: 99%
“…By implementing a detailed HAM model into an existing CFD solver (Fluent®) he was able to model the heat and moisture transport in the air and porous material simultaneously. The coupled model was validated using climate chamber experiments [12]. However, Steeman only modelled vapour diffusion as a transport mechanism in the porous material.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the storage capacity of the building envelope and furniture, moisture was absorbed by porous surfaces before reaching the other rooms. (Van Belleghem et al 2011;). …”
Section: Performance Of Moisture Absorption and Desorptionmentioning
confidence: 99%
“…The measurement results from this case were used to validate a CFD (computational fluid dynamics) model of a vertical downward blowing air curtain. Past studies [4][5][6][7] showed that CFD can be a useful tool for heat transfer assessment in buildings and building applications. This CFD model was then used to perform a parameter study from which the correlation between various parameters (outlet velocity, nozzle width, door geometry) and the heat transfer can be determined.…”
Section: Introductionmentioning
confidence: 99%